Farming, Education and Migration: Understanding Rural Youth in Northern Ecuador - Eche-Enriquez, Mauricio David; Vivas-Vivas, Ramiro José (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
This paper aims at analysing and presenting the findings regarding migration aspirations of agricultural High school students in northern rural Ecuador. Using a quantitative approach, it analyses 366 surveys from agricultural high schools’ students in three agricultural cantons located in different geographic regions: Coast, Highlands and Amazon. The migration drivers are low prices of agricultural produce, low wages and lack of technical support to agriculture. A big share does not intend to work in the agricultural sector in the Highlands and Coast; contrarily to the Amazon region. More than half of the respondents has aspirations to migrate to study in urban centres, and search for better economic and labour opportunities. Aspiration to migrate has a negative correlation with agriculture profitability. It is positive with parents’ land ownership, which is determined by the lack of interest to study agriculture at university that increases the scarcity of rural labour force and young successors to take up agriculture.